Brand analysis of the mark Fairtrade - Němcová, Kristýna (2012)
Fairtrade is a relatively young brand on the Czech market that is really interesting by its nature. The mark does not seek preferentially to maximize profits from the sale, but is interested in the ethical conduct of production of the goods in developing countries and fair rewarding today often disadvantaged workers and farmers. The aim of my thesis is to analyze the Fairtrade mark on the Czech market and to reveal the brand perception by consumers based on my own research. The theoretical part is concerned with the meaning of a brand, its features, brand equity and also describes the historical development of the mark Fairtrade. In the practical part I concentrate on the real analysis of the Fairtrade and based on the results from my research I find out the overall brand image in the minds of consumers. In conclusion based on the obtained results I try to formulate appropriate recommendations, which could help the mark in the future to improve the image and the market position.